Swelling of Steel Film by Hydrogen Absorption at Cathodic Potential in Electrolyte. Issue 6 (2nd April 2020) - Garai, Debi; Carlomagno, Ilaria; Solokha, Vladyslav; Wilson, Axel; Meneghini, Carlo; Morawe, Christian; Murzin, Vadim; Gupta, Ajay; Zegenhagen, Jörg
Abstract : An ≈4 nm FeCrNi film, deposited on a Ru/B4 C multilayer (ML), is used to study cathodic hydrogen charging in electrolyte. A thin film on a ML allows obtaining precise quantitative information on surface metal composition and oxidation state using the X‐ray standing wave technique combined with near‐edge X‐ray absorption spectroscopy. The metal composition is found being close to the composition of stainless steel (SS) 304, and, as for bulk steel, the outer 2 nm passive layer, consisting of oxidized iron and chromium, is depleted of nickel. Overall, it is found that the film represented a useful replica of the surface of bulk steel. Following exposure to 0.1 m KCl electrolyte at −0.6 V versus Ag/AgCl, 11.3 (±3)% swelling of the film by hydrogen absorption is observed. The estimated absorbed amount is exceeding reported bulk absorption under similar conditions by more than an order of magnitude. Strong hydrogen absorption appears to be enabled by the 2D character of the thin film, i.e., a significantly lower associated strain energy compared with bulk absorption. The strong surface swelling is suggested to be related to the lowering of the pitting corrosion resistance of SS surfaces reported following hydrogen exposure. Abstract : Precise quantitative information on surface metal composition and oxidation state of steel surfaces is obtained using a 4 nm film and X‐ray standing waves combined with near‐edge X‐ray absorption spectroscopy. Exposure to 0.1 m KCl at −0.6 V leads to strong swelling by hydrogen absorption, apparently related to correspondingly the observed lowering of the pitting corrosion resistance of stainless steel.